Procesos y modelos en el devenir del turismo en Argentina - Mantero, Juan Carlos (Revista Turismo em Análise, 2000)
The results from a near future touristic activities interpretation, allows us to identify three major development touristic models the handicrafts, the industry and the trade tourism. ln order to evaluate the near future activities in Argentine will be necessary to face the integrated challenge development of tourism opportunities. It is necessary to adopt a trade tourism model, which allows to assume the handicriate tourism options.